Effects of mixing water temperatures on properties of one-part alkali-activated slag paste. (10th January 2021) - Almakhadmeh, M.; Soliman, A.M.
Highlights: Initial mixing water temperature will affect the early dissolution rate for solid activator. Initial mixing water temperature can extend AAS slump life. Initial mixing water temperature has minimal effect on later strength. Initial mixing water temperature had a great influence on early deformation. Abstract: During hot and cold weather, initial mixing water temperature is a critical parameter in controlling the fresh and hardened properties of cement-based materials. With the advent of Alkali Activated Materials (AAMs), the effectiveness of such a technique becomes questionable as the hydration mechanism differs from that of the ordinary Portland cement (OPC). Therefore, this study focuses on evaluating the effects of initial mixing water temperature on the performance of one-part Alkali Activated Slag (AAS). Various AAS mixtures prepared by different mixing water temperatures (i.e. 0 °C, 10 °C, 20 °C, and 30 °C) were tested. Fresh and hardened properties, including mini-slump, slump loss rate, setting time, the heat of hydration, compressive strength, and shrinkage, were investigated. Results reveal that the initial mixing water temperature plays a dominant role in controlling solubility and dissolution rates for different ingredients (i.e. solid activator and slag). This, in turn, had affected the hydration process and consequently the development of various properties. Slump life and setting time were found to extend as the initial mixing water temperature reduced while the strength was not harmed. Saving energy consumed for warming water during cold weather concreting will also increase concrete sustainability. It is anticipated that these findings will pave the way for a broader implementation of such green sustainable materials in the construction sector.